2011
DOI: 10.1364/oe.20.000474
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state ab initio laser theory for N-level lasers

Abstract: We show that Steady-state Ab initio Laser Theory (SALT) can be applied to find the stationary multimode lasing properties of an N-level laser. This is achieved by mapping the N-level rate equations to an effective two-level model of the type solved by the SALT algorithm. This mapping yields excellent agreement with more computationally demanding N-level time domain solutions for the steady state.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 16 publications
4
64
0
Order By: Relevance
“…As long as the presence of this second lasing mode does not violate the SIA, the corresponding two-mode lasing solution is considered stable (as was previously verified using FDTD simulations [18,34,35]). As we will demonstrate through a comparison to timedependent solutions of the MB equations, this simple criterion can not be applied for nearly degenerate modes.…”
Section: Short Review Of Saltsupporting
confidence: 53%
See 2 more Smart Citations
“…As long as the presence of this second lasing mode does not violate the SIA, the corresponding two-mode lasing solution is considered stable (as was previously verified using FDTD simulations [18,34,35]). As we will demonstrate through a comparison to timedependent solutions of the MB equations, this simple criterion can not be applied for nearly degenerate modes.…”
Section: Short Review Of Saltsupporting
confidence: 53%
“…This is the case described by SALT, in which the MB equations are simplified to a set of time-independent, non-Hermitian, nonlinear and coupled Helmholtz equations. The solutions of these SALT equations are much more efficiently calculated than those of the MB equations [18,25,34,35].…”
Section: Short Review Of Saltmentioning
confidence: 99%
See 1 more Smart Citation
“…II) simplify the general MB equations by removing the time dependence for steady-state modes, which allows SALT solvers to be potentially far more efficient than previous timedomain approaches [13,14], while providing comparable accuracy [15,16]. However, all earlier approaches to SALT required the intermediate construction of a specialized constant-flux (CF) basis for the laser modes.…”
Section: Introductionmentioning
confidence: 99%
“…It makes no a priori assumptions about the geometry of the laser system, treats the open (non-Hermitian) character of the laser system exactly, and the nonlinear hole-burning interactions between the laser modes to infinite order. More realistic and quantitative laser modeling typically requires treating a gain medium with three, four, or more relevant atomic levels, but it has been shown that for the steady-state properties, under the same assumptions as SALT, the semiclassical equations can be reduced to an effective two-level (MB) system with renormalized parameters and solved with essentially the same efficiency as two-level SALT [16,27]. SALT can also be used to describe quantum properties of lasers by combining the nonlinear scattering matrix of SALT with input-output theory, leading specifically to a general formula for the linewidth of each mode in the nonlinear steady state [28].…”
Section: Introductionmentioning
confidence: 99%